Case report: Clinical and genetic analysis of a family with nonsyndromic auditory neuropathy - Jiang, Lan; Xu, Hongen; Liu, Danhua; Zhang, Sen; Xu, Ying (Frontiers in Pediatrics, 2022)
Background: Auditory neuropathy (AN) is a hearing disorder caused by the failure of inner hair cells, auditory nerve synapses and/or auditory nerves. With the development of high-throughput sequencing technology, the genetic factors of AN have been revealed, and genetic testing has become an important tool for identifying different types of AN. Case description: To study the genetic cause of non-syndromic auditory neuropathy in a Chinese family. The family was from Henan Province with three affected individuals. The audiological examinations were performed on the affected individuals, and whole-exome sequencing was carried out on the proband. The suspected pathogenic variants screened by the bioinformatic analysis were validated using Sanger sequencing in the family members. We identified three novel variants c.3277G>A(p.Glu1093Lys), c.4024-4G>T, and c.898-2A>G of the OTOF gene in the three children with AN. The first two variants were inherited from their father, and the third variant was inherited from their mother. A minigene assay was designed to test the effect of c.4024-4G>T on splicing. The variants c.4024-4G>T and c.898-2A>G could be classified as likely pathogenic/pathogenic according to the ACMG guidelines for genetic variants. Conclusion: New pathogenic/likely pathogenic variants of the OTOF gene were identified in a family with AN, enriching the mutational spectrum of the OTOF gene.